Public Sector Debt Definitions and Reporting in Low-Income Developing Countries. (Policy Papers; Policy Paper ;, 2020)
Increasing public debt vulnerabilities in low-income developing countries (LIDCs) have heightened the need for fuller and more transparent accounting of public sector debt (PSD). The framework for reporting on public sector debt is sound. But there is room for LIDCs to further improve their compilation, reporting, and dissemination of public sector debt data in international databases and more broadly the public domain.